Increased SIRT1 Concentration Following Four Years of Selenium and Q 10 Intervention Associated with Reduced Cardiovascular Mortality at 10-Year Follow-Up-Sub-Study of a Previous Prospective Double-Blind Placebo-Controlled Randomized Clinical Trial - Opstad, Trine Baur; Alexander, Jan; Aaseth, Jan; Larsson, Anders; Seljeflot, Ingebjørg; Alehagen, Urban (Antioxidants, 2023)
: Selenium and coenzyme Q (SeQ ) possess antioxidant and anti-inflammatory properties, potentially mediated via Sirtuin1 (SIRT1). We aimed to investigate the influence of a SeQ intervention on SIRT1 concentration, with potential interactions with microRNAs. : In this sub-study of a prospective double-blind placebo-controlled clinical trial, healthy subjects (mean age 76 years) were randomized to receive an active treatment ( = 165, combined 200 µg/day of Se and 200 mg/day of Q ) or a placebo ( = 161). SIRT1 concentration and microRNAs were measured with ELISA and PCR, respectively. : After four years, SIRT1 concentration was increased in the active treatment group, with mean (SD) ng/mL of 469 (436) vs. 252 (162), < 0.001, and decreased in the placebo group, 190 (186) vs. 269 (172), = 0.002, and the differences between the groups were significant ( = 0.006, adjusted). Those who suffered CV death during a 10-year follow-up ( = 25 and = 52 in the active treatment and placebo groups, respectively) had significantly lower baseline SIRT1 concentrations compared to the survivors ( < 0.001). MiR-130a-3p was significantly downregulated during the intervention and correlated inversely with SIRT1 at baseline (r = -0.466, = 0.007). : The increased SIRT1 concentration after the SeQ intervention associated with reduced CV mortality, partly mediated via miR-1303a-3p, suggests that SIRT1 is an additional mediator of the intervention, preventing vascular ageing.